Influence of the type of load graphs on the service life transformers 33/11 Kv at substation "Kabun-1" (Syrian Arab Republic) - E. Yu. Abdullazyanov; E. I. Gracheva; A. Alzakkar; S. Valtchev; N. Mestnikov (Известия высших учебных заведений: Проблемы энергетики)
Power transformers are one of the main components of power supply systems needed to reliably supply electricity to consumers. As we know, the value of the allowable load of transformers is determined by the value of the allowable heating of structural elements, on which the service life of transformer period depends. Reliable data on the technical condition of the structural elements of transformers is the decisive information for making decisions on the replacement and maintenance of transformers. METHODS. To assess the service life of transformers, methods were used to evaluate the statistical parameters of consumer load graphs, load factors and the heating temperature of the windings of transformers with a capacity of Sn.T = 20 MVA, a voltage of 33/11 kV at substation Kabun-1. THE AIM. The aim of the work is to evaluate the service life of the transformers at substation Kabun-1 (Syrian Arab Republic) with various options for the type of load power consumption graph (first; second; third). THE RESULTS. The main statistical parameters of the characteristics of the original and proposed options of load power graphs (active, reactive and apparent) per day of transformers, the main electrical consumer of which is the spinning and weaving factory, are determined. Approximating functions of daily graphs of power loads of transformers, from which the spinning and weaving factory receives power (first and second approximations), have been developed. It is proved that with the considered options for shifting the time of the start of work of electrical consumers - with the third option -the maximum load power is reduced by 12.8%, load variation is reduced from 0.33 to 0.17 in relation to the second option for the subdivisions of the spinning and weaving factory. It has been established that for all the considered options, the average value of the load power of the transformers at substation Kabun-1 is constant. The laws of change in the relative value of the service life of transformers during the implementation of various technical measures are determined.